The Role of Religious Leaders in Conducting Islamic Religious Education in The Community - Patoni, Achmad; Rifai, Muh Khoirul (JURNAL AL-TANZIM, 2022)
This study aims to understand the critical role of religious leaders in Islamic education so that people understand that something they learn will be helpful in their lives in this world and the hereafter so that they will not feel a loss in learning and applying Islam in their lives. This research uses a case study research method with a qualitative approach. Researchers conducted intensive interviews, involvement observations, and collection of documentation as data mining directly in the field and analyzed by describing events in the field. This study found that the role of religious leaders as leaders in carrying out Islamic religious education is carried out through example, practice and action, ibrah and advice, dialogue, and non-formal coaching and management. This research has implications for the importance of example, practice, deeds, ibrah and advice, dialogue in managing non-formal educational institutions.